Pengabdian Meningkatkan Pemahaman Numerasi Siswa SDN Sutorejo I Melalui Program Kampus Mengajar 6 - Muhammad Juraish Baihaqi; Fauzie Senoaji; Endang Indartuti (Jurnal Informasi Pengabdian Masyarakat, 2023)
The Teaching campus is one of the Merdeka Learning Campus Merdeka (MBKM) programs that involves students to shape learning, especially for elementary school (SD) and junior high school (SMP) level children as part of strengthening literacy and numeracy learning so that students can become teacher partners in carrying out creativity and innovation in the world of education. Increasing students' understanding of numeracy is one of the efforts of our group work program of campus teaching students batch 6 which focuses on increasing the numeracy knowledge of SD Negeri Sutorejo I 240 students. In the implementation of numeracy we apply to students learning activities of numeracy students of addition, division, multiplication, and subtraction. Flat shapes, as well as drill problems at the upper levels to train students to make it easier to understand basic math. The type of research used is descriptive qualitative with the techniques used in collecting data, namely using interviews, observation, and documentation techniques. This study aims to determine the role and duties of teaching campus students in helping to improve numeracy at SD Negeri Sutorejo I 240, Surabaya. Based on this research, it is concluded that teaching campus students have an important role in improving literacy, numeracy in schools.